2019
DOI: 10.1007/978-3-030-11723-8_9
|View full text |Cite
|
Sign up to set email alerts
|

Multi-institutional Deep Learning Modeling Without Sharing Patient Data: A Feasibility Study on Brain Tumor Segmentation

Abstract: Deep learning models for semantic segmentation of images require large amounts of data. In the medical imaging domain, acquiring sufficient data is a significant challenge. Labeling medical image data requires expert knowledge. Collaboration between institutions could address this challenge, but sharing medical data to a centralized location faces various legal, privacy, technical, and data-ownership challenges, especially among international institutions. In this study, we introduce the first use of federated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
288
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 366 publications
(291 citation statements)
references
References 19 publications
3
288
0
Order By: Relevance
“…One of the major challenges in machine learning analysis of biomedical imaging data is the lack of large curated and annotated training datasets, primarily because of time effort and domain expertise required for manual segmentations and classifications of tissue regions and micro-anatomic structures, such as nuclei and cells, as well as because of privacy and ownership concerns of source datasets. Some initial studies in the field of distributed learning in medicine attempted to address the data privacy and ownership challenge (Chang et al, 2018b;Sheller et al, 2018). These approaches need more investigation and adoption to facilitate collaboration across multiple medical institutions.…”
Section: Resultsmentioning
confidence: 99%
“…One of the major challenges in machine learning analysis of biomedical imaging data is the lack of large curated and annotated training datasets, primarily because of time effort and domain expertise required for manual segmentations and classifications of tissue regions and micro-anatomic structures, such as nuclei and cells, as well as because of privacy and ownership concerns of source datasets. Some initial studies in the field of distributed learning in medicine attempted to address the data privacy and ownership challenge (Chang et al, 2018b;Sheller et al, 2018). These approaches need more investigation and adoption to facilitate collaboration across multiple medical institutions.…”
Section: Resultsmentioning
confidence: 99%
“…The Intel corporation has started a collaboration with the University of Pennsylvania and 19 other institutions to advance real world medical research using the federated learning. They showed that a deep learning model which is trained by traditional approach on pooled data, can be trained up to 99% of the pooled accuracy using the federated learning approach [53].…”
Section: Discussionmentioning
confidence: 99%
“…The federated learning approach is used for semantic segmentation without sharing patient data by the multi-institutional collaboration. Federated learning provides better accuracy for semantic segmentation, with respect to the model that is trained on sharing data [145].…”
Section: Feasibility Studies On Segmentationmentioning
confidence: 99%